Gender Features of Myocardial Revascularization Results in Patients with Stable Coronary Artery Disease, Multivascular Coronary Injury and Reduced Left Ventricular Systolic Function - Kucheriava, M. V.; Mankovskiy, G. B.; Rudenko, N. M. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To investigate the course, quality of life and risk factors depending on gender in patients with stable isch-emic coronary disease, multivascular coronary injury and reduced left ventricular systolic function Materials and methods. In a one-center study of the Ukrainian Children’s Cardiac Center, Clinic for Adults analyzed data from 107 patients with coronary artery disease, multivascular coronary artery injury and reduced left ventricular systolic function (LV EF below 35%), who underwent complete revascularization from January until December 2020. Among those surveyed were 67 (62.6%) men and 40 (37.4%) women aged 54 to 83 years. Myocardial infarction was diagnosed in 95 (88.7%) patients. Hypertension was diagnosed in 50 (74.6%) men and 35 (87.5%) women. Diabetes was registered in 13 (19.4%) men and 14 (35.0%) women. Results and discussion. According to the multivariate analysis, the most significant factors in reaching the endpoint during the annual follow-up after CABG and PCI were: worse left ventricular systolic function; the presence of diabetes mellitus; and lack of postoperative statin therapy. Conclusion. Gender features in long-term results after myocardial revascularization were revealed. Women were more likely to complain of angina in the postoperative period and rather hospitalized than men, but they were less likely to undergo myocardial revascularization. The quality of life after CABG and PCI in female patients was slightly reduced compared to that in men. After the intervention, men were less likely to take statins than women. Regardless of the type of myocardial revascularization in women, LV EF was higher than in men.